Assessment innovation of mahārah kalam in Arabic language textbooks for first grade of Islamic elementary school - Arini Daeng Pasau; Imam Fauji (Research and Development in Education (RaDEn), 2025)
This study aims to develop an innovation in the assessment of maharah kalam in the Arabic language textbook for first grade of Islamic Elementary School of Muhammadiyah. The focus of this study is to make it easier for teachers to evaluate the level of mahārah kalam of students before learning, so that learning can be adjusted to the abilities of each student in the class. This study is expected to be a breakthrough in the world of education, helping teachers understand students' initial abilities effectively. The method used is descriptive qualitative, which aims to describe, explain, and validate the phenomena studied. Primary data comes from Arabic language textbooks published by the Provincial Board of Muhammadiyah of East Java, while secondary data includes related books and journals. Assessment is an important element in learning, helping teachers evaluate the success of the learning process. One form of assessment used is performance assessment, which measures students' psychomotor abilities through observation of speaking practice. The assessment of mahārah kalam at the first grade of elementary school level involves practicing paired dialogues by memorizing material from textbooks. The aspects assessed include pronunciation, intonation, expression, and fluency. The assessment results show the categories of quite competent, competent, and very competent. With this innovation, teachers are expected to be able to create more relevant and effective learning.